A current fed two-inductor boost converter for grid interactive photovoltaic applications - Li, Q.; Wolfs, Peter (University of Queensland, 2004)
A current fed two-inductor boost converter is combined with a low frequency unfolder stage to produce a Module Integrated Converter (MIC) for photovoltaic applications. A two-phase buck converter with an interphase transformer is modulated to produce a rectified sinusoid waveform as an input to the fixed duty cycle two-inductor boost cell. The boost cell features an integrated magnetics approach to combine the two inductors and the transformer cores, non-dissipative snubbers to recover switching losses and silicon carbide output rectifiers. The MIC interfaces with the mains via an unfolder stage which uses optically driven mosfets as switching elements. Experimental results for a converter with an average power of 50 W are provided.